Systematic review of Doppler for detecting intrapartum fetal heart abnormalities and measuring perinatal mortality in low‐ and middle‐income countries. Issue 2 (5th December 2019) - Plotkin, Marya; Kamala, Benjamin; Ricca, Jim; Fogarty, Linda; Currie, Sheena; Kidanto, Hussein; Wheeler, Stephanie B.
Abstract: Background: Using Doppler to improve detection of intrapartum fetal heart rate (FHR) abnormalities coupled with appropriate, timely intrapartum care in low‐ and middle‐income countries (LMIC) can save lives. Objective: To review studies using Doppler to improve detection of intrapartum FHR abnormalities and intrapartum care quality in LMIC health facilities. Search strategy: PubMed, Web of Science, Embase, Global Health, and Scopus were searched from inception to October 2018 by combining terms for Doppler, perinatal outcomes, and FHR monitoring. Selection criteria: Selected studies compared Doppler and Pinard stethoscope for detecting/monitoring intrapartum FHR, or described provider and maternal preferences for FHR monitoring in LMIC settings. Data collection and analysis: Two team members independently screened and collected data. Risk of bias was assessed by Cochrane EPOC criteria. Results: Eleven studies from eight countries were included. Doppler was superior at detecting abnormal intrapartum FHR as compared with Pinard stethoscope, but was not associated with improved perinatal outcomes. Using Doppler on admission helped to accurately measure perinatal deaths occurring after facility admission. Conclusion: Studies and program learning are needed to translate improved detection of FHR abnormalities to improved case management in LMICs. Doppler should be used to calculate a facility indicator of intrapartum care quality. PROSPERO registration: CRD42019121924. Abstract : Doppler is superior to Pinard stethoscope for detecting fetal heart rate abnormalities. Without a focus on prompt clinical management, improving perinatal outcomes will be difficult.